Challenges to Legitimacy at the Forest Stewardship Council - Schepers, Donald H. (Journal of business ethics, 2010)
The Forest Stewardship Council (FSC) is a global private governance system overseeing the sustainability and biodiversity of the world forestry system through certification of forests and forestry processes and products, and is perceived as the strongest of the various certification schemes available (Domask, Globalization and NGOs: Transforming Business, Government, and Society, 2003; Gulbrandsen, Global Environmental Politics, 2004). It has seen more success in developed than developing countries in terms of amount of forest certified and number of chain-of-custody certificates issued, raising questions as to its ability to promote biodiversity Gulbrandsen, Global Environmental Politics, 2004). A number of challenges have risen to the pragmatic and moral legitimacy of the FSC as a global governance system: alternative certification schemes, output and market access, cost of certification, plantations, and illegal logging. I examine each of these challenges as they pertain to the dimensions of pragmatic and moral legitimacy of the FSC. I conclude with a discussion of theoretical implications for global governance systems using ecolabel schemes, as well as a discussion of practical implications for the FSC in particular.